(3JSgjd GdahGFO hJcejd GdebGUOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3jhSa Hf UhLj Hf Ndjd s)
(3ChdgG (B:s
(3bGd MGeOkG Gddg QH GdYGdejf gPG cJGH aj GdfMh LYdJg HYhf Gddg eSJhajkG dCUhdg s
(3BNQgG (B:s
(3hRjOJ jGA aj JCjjO, hef fHCj GdeQSdjf, hedGjg hedGjge hgPG eeG jfbGO Edjg hdG jbGS Ydjg Je cJGH s
(3GdfSNI HgG MhGTs
(3GdfSNI YdjgG MhGTj HgGA GdOjf GHf Ybjd TQM Hg GdJSgjd h SeGg (B" (3GdeSGYO (B" (3HNW GdfGSN faSgs
(3hHgG fXGe GdJYbjHIs
(3aj GdeYgO fSNI CNQis
(3GfXQgG aj GdLRA GdChd (B35 (3fMh s
(3fSNI KGfjI s
Keywords: (3GdfMhs